Earnings management in business groups during the SARS-CoV-2 pandemic - Michał Comporek (Central European Economic Journal (CEEJ), 2024)
This paper aims to assess the influence of the SARS-CoV-2 pandemic on the accrual-based earnings management patterns in non-financial business groups in the Warsaw Stock Exchange (WSE). This study contributes to the existing literature by considering earnings manipulation behaviours in assessing the reporting data quality, both in consolidated financial statements of business groups and individual financial statements of parent undertakings. The research methods are based on the Modified Jones Model with the simultaneous separation of individual subcategories of accruals via cross-sectional analysis and time-series data approach (separately for each business group). Empirical findings supported the presumption that earnings manipulation schemes in the SARS-CoV-2 transitional (2020) and crisis (2021) periods differed statistically compared to the previous 2019 and 2020 years, respectively. Moreover, this article proved that the company's potential financial distress could imply accrual-based earnings management behaviours and moderate the association between the SARS-CoV-2 pandemic and earnings manipulations activities. Finally, the obtained results confirmed that although business groups have an expanded set of balance sheet policy instruments, the quality of earnings reported in the individual financial statements of parent undertakings and the consolidated financial statements of business groups were similar during the SARS-CoV-2 pandemic.
Keywords: G10; G32; M41; 330; accrual-based earnings management; business group; parent undertakings; the SARS-CoV-2 pandemic